Beyond the basics : the management guide for library and information professionals. New York: Neal-Schuman, 2003 - Rega, Liliana Laura (2006)
Fil: Rega, Liliana Laura. Universidad del Salvador. Biblioteca Central Padre Guillermo Furlong, S.J.; Argentina.